2014
DOI: 10.1021/bc500289u
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Fatty Acid Vesicles through Newly Synthesized Bolaamphiphile–DNA Conjugates

Abstract: The surface functionalization of fatty acid vesicles will allow their use as nanoreactors for complex chemistry. In this report, the tethering of several DNA conjugates to decanoic acid vesicles for molecular recognition and synthetic purposes was explored. Due to the highly dynamic nature of these structures, only one novel bola-amphiphile DNA conjugate could interact efficiently with or spontaneously pierce into the vesicle bilayers without jeopardizing their self-assembly or stability. This molecule was syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Since it has recently been shown that both peptide and nucleic acid precursors can be formed in a prebiotic environment from simple building blocks of unified origin, we suggest that synergistic activity such as that demonstrated here may have led to the selection of functional chimeras. Together with other recent results demonstrating structural and functional synergy in NA‐pep systems and also synergy between simple prebiotically relevant molecules from different families, such as NA‐lipid, pep‐lipid, and sugar‐pep, the current study shows the rapid progression in complexity and systems chemistry that would have facilitated a large repertoire of functions.…”
Section: Discussionsupporting
confidence: 77%
“…Since it has recently been shown that both peptide and nucleic acid precursors can be formed in a prebiotic environment from simple building blocks of unified origin, we suggest that synergistic activity such as that demonstrated here may have led to the selection of functional chimeras. Together with other recent results demonstrating structural and functional synergy in NA‐pep systems and also synergy between simple prebiotically relevant molecules from different families, such as NA‐lipid, pep‐lipid, and sugar‐pep, the current study shows the rapid progression in complexity and systems chemistry that would have facilitated a large repertoire of functions.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to vesicles with their confined aqueous volume, other even simpler compartment systems, are equally worth considering, since they may have played important roles before cell-like vesicular compartments existed, see Figure 1 . Moreover, it is also reasonable to question the idea of a very early encapsulation of reaction networks into an aqueous lumen because the creation of catalytic networks or the execution of catalytic or self-assembly processes can also be facilitated by association of their molecular components with surfaces [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The same rationale could also apply to aggregates that possess boundaries that are not as clearly delineated as cellular membranes.…”
Section: Models For Prebiological Compartmentalizationmentioning
confidence: 99%
“…Even in the presence of chemical systems, like coacervates, the necessity of a direct association with the structure has to be postulated, considering the fact that short RNA strands can diffuse out the coacervate structures [ 117 ]. Obviously, the type of molecules that can be associated by tethering or electrostatic interactions long enough to permit catalysis is limited even though reports exist demonstrating the spontaneous inoculation of amphiphilic DNA derivatives into fatty acid vesicles [ 49 ]. Nonetheless, the potential for a co-localization on a surface of a relatively complex reaction network is plausible because essential functions on or within amphiphile compartment boundary cores have been observed: systems catalyzing transformation of precursor molecules into amphiphiles [ 48 ], or energy uptake [ 123 , 141 , 143 ].…”
Section: Possible Roles Of Prebiotic Compartmentsmentioning
confidence: 99%
“…For instance, micelle formation in bolas was ascribed to the stabilization of such structures by hydrogen bonding and aromatic stacking, in addition to the hydrophobic interactions. The other type of structure largely reported in the literature with bolas is vesicles . Here also, the vesicle formation was mostly attributed to electrostatic interactions, hydrogen bonding, head group size, effective charge, π–π stacking, presence of additives, and the method of preparation.…”
Section: Bolaamphiphile Self‐assemblymentioning
confidence: 83%